Dietary, immunological, surgical, and other emerging treatments for pediatric refractory status epilepticus. (May 2019) - Arya, Ravindra; Rotenberg, Alexander
Highlights: Class 1 HYBERNATUS trial does not support hypothermia for RSE/SRSE. Brexanolone not better than placebo in a double blind trial. Ketogenic diet showed efficacy in 20%–90% of patients in larger (n = 8–17) series. Other immunological treatments may have role in a selected group of RSE/SRSE patients. Limited evidence for surgical and other treatments for RSE/SRSE. Abstract: Purpose: To summarize the evidence regarding dietary, immunological, surgical, and other emerging treatments for refractory status epilepticus (RSE)/super-RSE (SRSE). Methods: Narrative literature review including relevant human studies. Results: Hypothermia and brenaxolone were tested in randomized controlled trials for RSE/SRSE management, while other interventions have only limited evidence for their efficacy and safety. Clinical trials including the HYBERNATUS study found the efficacy of therapeutic hypothermia to be no better than placebo for RSE/SRSE, and raised concerns about its safety. Ketogenic diet has shown possible efficacy in RSE/SRSE in several case series, with electrographic seizure resolution within 7 days in 20%–90% patients in larger (n = 8–17) reports. A review of 37 pediatric patients reported seizure control with immunotherapy in only 7 patients. A phase 3 double-blind trial showed that brexanolone was no better than placebo for successful wean of 3rd line anesthetic agent(s) and freedom from RSE for ≥24 hours. Epilepsy surgery has been reported to successfully control seizures in small series; however, pre-surgical evaluation is confounded by ongoing ictal activity and anesthetic infusions. Vagus nerve stimulation was reported to be associated with cessation of RSE/SRSE in 21/28 patients in a review of anecdotal reports. There is no evidence for use of pyridoxine and magnesium outside of specific indications. Conclusions: There is only anecdotal evidence for dietary, immunological, surgical, and other treatments for RSE/SRSE, often confounded by multiple concurrent treatments, and heterogeneity in their use and assessment of outcomes. Clinical trials for therapeutic hypothermia and brexanolone have not shown a significant advantage over comparators.